1980
DOI: 10.1190/1.1441125
|View full text |Cite
|
Sign up to set email alerts
|

Movement of radon in overburden

Abstract: An analytical solution for simple one‐dimensional geometry establishes the basic theory of the movement of [Formula: see text] (radon) in overburden, involving diffusion and convection. The computer‐adapted finite‐difference method is then used to determine radon concentrations for the following more complex configurations: a two‐dimensional source, a vertical fault, a three‐dimensional source, and multilayered overburden. The key parameters are the radon concentration at the source, the diffusion coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Plots for CO2 in soil gas are shown in Figure 8 Informative reviews and case histories of radon use have been published fairly recently, as the technique gained renewed interest from the energy-related research of the 1970's [Tanner, 1978;Rubin, 1978;Soonawala and Telford, 1980;Kraner et al, 1964]. The use of helium in exploration is a recent development, and case histories are few but informative [Reimer et al, 1970;Dyck, 1976 Previous studies had yielded information on the role in the formation of the uranium deposits [Bowles and groundwater chemistry, and tritium data provided infor-Braddock, 1963; Bowles, 1968].…”
Section: Soil Gas Surveys At This and Other Deposits Have Revealed Vomentioning
confidence: 99%
“…Plots for CO2 in soil gas are shown in Figure 8 Informative reviews and case histories of radon use have been published fairly recently, as the technique gained renewed interest from the energy-related research of the 1970's [Tanner, 1978;Rubin, 1978;Soonawala and Telford, 1980;Kraner et al, 1964]. The use of helium in exploration is a recent development, and case histories are few but informative [Reimer et al, 1970;Dyck, 1976 Previous studies had yielded information on the role in the formation of the uranium deposits [Bowles and groundwater chemistry, and tritium data provided infor-Braddock, 1963; Bowles, 1968].…”
Section: Soil Gas Surveys At This and Other Deposits Have Revealed Vomentioning
confidence: 99%
“…Due to its unique physical and chemical properties, radon gas migration is related to various factors, and no agreement has been reached on the mechanism and principles underlying this process. Various studies have proposed different mechanisms of radon gas migration from underground strata to the surface (e.g., Wilkening and Watkins, 1976;Fleischer and Mogro-Campero, 1979;Soonawala and Telford, 1980;Varhegyi et al, 1992;Folger et al, 1997;Wattananikorn et al, 1998;Cameron et al, 2002;Le and Wang, 2006), including diffusion, convection, pore fluid, advection, and micro-bubbles as carriers, relay transmission, stress compression, and cluster theory. Nevertheless, different groups have uniformly reported that radon gas can migrate to the ground via micro-cracks and pores in the underground strata.…”
Section: Migration Of Free-state Radonmentioning
confidence: 99%
“…The fresh water that percolates into the rock fractures carries the radioactive gas that can travel several meters before escaping through some fracture, towards the surface, even considering the small half-life of this gas. The escape to the atmosphere occurs through the transport mechanism known as diffusion (Soonawala and Telford, 1980). Measurements were made at 5-m intervals along a line (Fig.…”
Section: Radon Gas Emanometrymentioning
confidence: 99%